Abnormal EEG Spectral Power and Coherence Measures During Pre-Motor Stage in Amyotrophic Lateral Sclerosis - Saroj Bista; Amina Coffey; Matthew Mitchell; Antonio Fasano; Stefan Dukic; Teresa Buxo; Eileen Giglia; Mark Heverin; Muthuraman Muthuraman; Richard G. Carson; Madeleine Lowery; Lara McManus; et al. (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Amyotrophic lateral sclerosis (ALS) is a multisystem neurodegenerative disorder characterized by progressive motor decline. Studies of electroencephalographic (EEG) activity during rest and motor execution have captured network changes in ALS. However, the nature of network-level impairment in the pre-motor activity in ALS remains unclear. Assessing the (dys)function of motor networks engaged prior to motor output is essential for understanding the motor pathophysiology in ALS. We recorded EEG in 22 people with ALS (PwALS) and 16 age-matched healthy controls during rest and isometric pincer-grip tasks. EEG spectral power and coherence were calculated during rest, pre-motor stage, and motor execution. In PwALS, significantly higher event-related spectral perturbations were observed compared to controls over electrodes representing a) contralateral prefrontal and parietal regions in theta band during pre-motor stage, b) contralateral parietal and ipsilateral motor regions in high-beta band during motor execution. Similarly, spectral coherence revealed abnormal EEG connectivity within 1) sensorimotor network during rest in theta band, 2) (pre)motor networks during pre-motor stage in low-alpha and high-beta bands, 3) Fronto-parietal networks during execution in high-beta band. Furthermore, the abnormal EEG connectivity during rest and execution (but not during pre-motor stage) showed significant negative correlation with clinical ALS-functional-rating-scale scores. Combining abnormal EEG connectivity from rest, pre-motor, and execution stages provided more powerful discrimination between patients and controls with a uniquely higher contribution of measures pertaining to the pre-motor stage. The results indicate that pre-motor functional activity reflects a different and unique aspect of network impairment, with potential for inclusion as biomarker candidates in ALS.